Mechanical Stress Stability of Flexible Amorphous Zinc Tin Oxide Thin-Film Transistors - Lahr, Oliver; Steudel, Max; von Wenckstern, Holger; Grundmann, Marius (Frontiers in Electronics, 2021)
Due to their low-temperature processing capability and ionic bonding configuration, amorphous oxide semiconductors (AOS) such as indium gallium zinc oxide (IGZO) are well suited for applications within future mechanically flexible electronics. Over the past couple of years, amorphous zinc tin oxide (ZTO) has been proposed as indium and gallium-free and thus more sustainable alternative to IGZO. The present study specifically focuses on the strain-dependence of elastic and electrical properties of amorphous ZTO thin-films sputtered at room temperature. Corresponding MESFETs have been compared regarding their operation stability under mechanical bending for radii ranging from 5\,mm to 2\,mm. Force-spectroscopic measurements yield a plastic deformation of ZTO as soon as the bending-induced strain exceeds 0.83\,%. However, the electrical properties of ZTO determined by Hall effect measurements at room temperature are demonstrated to be unaffected by residual compressive and tensile strain up to 1.24\,%. Even for the maximum investigated tensile strain of 1.26\,%, the MESFETs exhibit a reasonably consistent performance in terms of current on/off ratios between 6 and 7 orders of magnitude, a subthreshold swing around 350\,mV/dec and a field-effect mobility as high as 7.5\,cm$^2$V$^{-1}$s$^{-1}$. Upon gradually subjecting the transistors to higher tensile strain, the channel conductivity steadily improves and consequently, the field-effect mobility increases by nearly 80\,% while bending the devices around a radius of 2\,mm. Further, a reversible threshold voltage shift of about ${-}$150\,mV with increasing strain is observable. Overall, amorphous ZTO provides reasonably stable electrical properties and device performance for bending-induced tensile strain up to at least 1.26\,% and thus represent a promising material of choice considering novel bendable and transparent electronics.